Self-directed learning model and student independence in learning Buddhist religion of state senior high school I Tanjung - Diana Diana; Ayu Andriyaningsih; Sutiyono Sutiyono (International Journal of Science and Applied Science: Conference Series, 2025)
The purpose of this study was to examine the effect of the self-directed learning model on the learning independence of Buddhist students at State Senior High School I Tanjung. The problems encountered by students included a lack of initiative in overcoming problems and completing assignments, frequent copying of their friends' answers, a lack of responsibility in completing and submitting assignments, and a lack of discipline in the learning process. This study is expected to increase students' learning independence to achieve maximum learning outcomes. Self-Directed Learning is a learning model that allows students to manage the learning process independently, with initiative and freedom to learn. Through this approach, students can improve their abilities and achieve better learning outcomes. Self-Directed Learning aims to develop knowledge, skills, achievements, and individual development independently. This study used a quantitative approach with a survey method. The population in this study consisted of 92 respondents from State Senior High School I Tanjung who were Buddhist students in the 2024/2025 academic year. The results of this study indicate that the Self-Directed Learning model has a positive effect on the learning independence of Buddhist students at State Senior High School I Tanjung. Based on regression analysis, Self-Directed Learning contributes significantly to shaping students' learning independence, while some of their learning independence is influenced by other factors, such as the school environment, family, and peers. This confirms that the Self-Directed Learning model is one of the components in shaping learning independence.